Iron-functionalized nanoporous silica type SBA-15: Synthesis, characterization and application in alkene epoxidation in presence of hydrogen peroxide - Mahdieh Ghazizadeh; Alireza Badiei; Iran Sheikhshoaie (Arabian Journal of Chemistry, 2017)
Fe(III)salophen complex on a SBA-15 support functionalized with (3-aminopropyl)triethoxysilane as a linker. It has been synthesized and characterized by XRD, adsorption–desorption of nitrogen, SEM, FT-IR and UV–Vis. The formation of metal-salophen complex with the amino groups as connectors to the SBA-15 surface was confirmed. This material was successfully used as a heterogeneous catalyst for the epoxidation of alkenes and the effects of reaction time, different solvents and amount of catalyst on catalytic activity were investigated. This catalyst gave suitable and comparable yield and percentage conversion values. It is also stable and can be recycled and reused in the epoxidation of alkenes.